A question of (mis)alignment: innovation mandates and absorptive capacity routines. (14th October 2019) - Banerjee, Aneesh; Lampel, Joseph; Bhalla, Ajay
Abstract : Research suggests that effective R&D requires the right combination of inward‐looking and outward‐looking absorptive capacity routines. However, we do not have an adequate understanding of how these routines influence innovative output in R&D units with different mandates. In this paper, we argue that adopting an absorptive capacity routine would positively or negatively influence the R&D subsidiary's innovative output, depending on whether the routine is aligned or misaligned with the subsidiary's innovation mandate to 'exploit' existing knowledge or 'explore' new knowledge. We test this using data collected from a global packaged‐software firm with 14 international R&D subsidiaries that implemented six major absorptive capacity routines in the period 2000–2010. Our research provides new insights for both scholars and practitioners in R&D management, by showing that balancing of absorptive capacity routines should be considered in light of innovation mandates of subsidiaries as well as the firm. Our analysis also provides insights on why decision makers may still adopt misaligned routines.